Analisis Semiotika Roland Barthes Pada Lirik Lagu “Aisyah Istri Rasulullah” Syakir Daulay - Nanda, Rahmat Pike Pirnanda (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2023)
This research is motivated by the presence of a cover single entitled Religion, a song performed by a singer and actor from Aceh, entitled